Breastfeeding Duration More than 18 Months Possibly Lowers the Risk of Language Development Delay in Children Aged 18–35 Months - Faradilah, Andi; Rusyaidi, Andi Musafir; Jalaluddin, Syatirah; Savitri, Ary I (Kesmas, 2022)
Studies have demonstrated the benefits of breastfeeding (BF) on children’s cognitive function and language development. However, most cognitive and language tools used in these studies have limited ability to identify children’s language development delays. The Language Development Survey (LDS) is expected to provide detailed information on children’s language development. This study aimed to examine the association between BF duration and children’s LDS. A questionnaire was administered to 286 BF mothers to obtain information on their BF duration, and LDS was employed to assess children’s language development. Language delays were detected in 91 (31.8%) children (LDS-vocabulary) and 35.7% children (LDS-phrase). This study also found that children who were breastfed for ≤6 months and 7–18 months had an adjusted OR (AOR) of 0.86 of LDS-vocabulary, and 0.8 of LDS-phrase, whereas children who were breastfed for >18 months had AOR’s LDS-vocabulary of 0.57 and LDS-phrase of 0.46. This study found no significant association between BF duration and LDS score. Nevertheless, BF duration of >18 months possibly lowers the risk of children’s language development delay. More studies are required to investigate this observation’s relationship with children’s language development.